Towards Attainment of Kenya Certificate for Secondary Education: Role of School Culture in Kenya (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2023)
Empirical research revealed that Kenya is experiencing poor performance in the Kenya Certificate for Secondary Education (KCSE) within the context of subsidized secondary education adopted in 2008. School culture has been considered a central concept that changes how schools operate, improve educational results and is heavily influenced by its institutional norms and history which could be an obstacle to over all performances. The purpose of the study therefore was to determine school culture and its influence on KCSE attainment in Nandi Central Sub County Kenya. The study was guided by the following objectives: To establish form(s) of culture(s) that is/are practiced. To determine the relationship between school motto, vision, mission statement, to determine the relationship between school rules, regulations and the attainment of KCSE in public secondary schools in Kenya and to establish the relationship between Internal assessment exams and attainment of KCSE in public secondary schools in Kenya. This study adopted convergent triangulation mixed method research design; Pragmatic philosophical paradigm was employed. This study was guided by dual factor theory by Fredrick Herzberg 1957. The study was conducted in Nandi Central Sub-County, Nandi County involving 20 secondary schools. There were 352 respondents comprising of 20 principals, 81 form four class teachers and 251 form four students selected using simple random, stratified sampling and purposive technique.. The data from the study was collected using questionnaires, interview, document analysis and direct observation. Data generated from this study was both quantitative and qualitative. Analysis of quantitative data involved, use of inferential statistical analysis where data was coded and entered into a Statistical Package for Social Sciences (SPSS) version 26. In qualitative approach, data was analyzed thematically by organizing themes corresponding to the study objectives. The study revealed that, there was a statistically significant relationship between forms of cultures practiced and attainment of KCSE in Kenya (p=0.019